2016
DOI: 10.1002/elps.201500535
|View full text |Cite
|
Sign up to set email alerts
|

Picomolar detection of carcinoembryonic antigen in whole blood using microfluidics and surface‐enhanced Raman spectroscopy

Abstract: Carcinoembryonic antigen (CEA) is a wide-spectrum biomarker. Clinically, we generally use serum sample to detect CEA, which needs to be centrifuged to pretreat the raw blood sample. In this study, we realized direct CEA detection in raw blood samples exploiting microfluidics. The LOD was as low as 10(-12) M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Zou et al. developed protocol for detection of carcinoembryonic antigen in whole blood with the use of magnetic particles carrying capture antibody . The detection antibody and Raman‐reporter were attached to the gold nanoparticle.…”
Section: Current Application Trendsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zou et al. developed protocol for detection of carcinoembryonic antigen in whole blood with the use of magnetic particles carrying capture antibody . The detection antibody and Raman‐reporter were attached to the gold nanoparticle.…”
Section: Current Application Trendsmentioning
confidence: 99%
“…Components creating a complex laminar flow pattern that enables mixing flow without the use of any external energy, e.g. zig–zag channels , serpentine channels , pillars , or branching channels belong to the most common designs.…”
Section: In‐solution Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now the incorporation of antibody into the microfluidic-SERS system has been reported by many groups. For example, Zou et al [ 140 ] reported the CEA detection in raw blood samples exploiting microfluidics. After capturing CEA by antibody coated magnetic nanoparticle, the immunocomplex were then mixed with AuNPs coated with both antibody and Raman tag to detect CEA in whole blood with picomolar precision.…”
Section: Microfluidics-sersmentioning
confidence: 99%